Analysis of the Impact of Microclimate in a Roof Space on a Gothic Truss Construction - Renata Korenkova; Peter Krusinsky; Peter Pisca (Communications - Scientific letters of the University of Zilina, 2013)
The research in the field of historical trusses, carried out at the workplace of authors for a long time, is focused on monitoring and analysing microclimate with the aim of specifying environmental conditions that would be suitable for preservation of a historical structure for further generations. Currently, this investigation is running together with a blanket screening of historical trusses in Slovakia [1 and 2]. In each truss, there was recorded the general technical state as well as the way of ventilation in a roof space. To define the impact of microclimate in a roof space on the lifetime period and sustainability of a historical truss, long-term measurements of features regarding both a roof space and its surroundings are made. The gothic truss over the gothic Roman-Catholic church of the Most Holy Body of Christ was chosen as an experimental truss for this type of analysis because it is very well-preserved.